TOP (TOILET OTOMATIS PASIEN): RANCANG BANGUN INOVASI TOILET PADA TEMPAT TIDUR PASIEN MUNTABER DAN KOLERA - Liana, Margiasih Putri; Aditya, Emy; Sujarwanto, Tri; Prakosa, Pebrian Tunggal (Program Kreativitas Mahasiswa - Karsa Cipta, 2013)
Diarrhea and cholera are an infection of the digestive system with watery stools conditions that can not be controlled disposal. Current technology is just a simple bed with a hole in the center, or bipots. Because of these conditions we made TOP (Toilet Otomatis Pasien) which is an automatic toilet design with mass measurement technology. The main cause of death of patients is the lack of the amount of fluids in the body. By knowing the mass of feces, doctor can control body fluids and provide appropriate treatment. TOP extremely hygienic design with a channel that connect directly to a portable dump. TOP tools will help the medical world to handle muntaber and colera patient.